Partisipasi Guru Agama Kristen Terhadap Pendidikan Dalam Mewujudkan Visi Misi Indonesia Emas 2045 - Sozanolo Zamasi; Elfin Warnius Waruwu (Jurnal Magistra, 2024)
This research is an in-depth study of the important role of Christian Religion teachers' participation in the Indonesian educational context and their efforts in achieving Indonesia's Golden Vision 2045. Through qualitative methods and library studies, this research explores the impact and contribution of Christian Religion teachers to student character development as well as the implementation of Christian values in the education curriculum. The literature analysis investigated the pattern of Christian Religious teachers' participation in guiding students, emphasizing the importance of ethics and morals in the formation of the next generation. The findings from this study are expected to provide insights into how Christian Religious teachers' participation can significantly contribute to the understanding of Christian values and the achievement of the national goal of creating a just, equitable and highly competitive society by 2045. The conclusion of this article provides a holistic picture of the importance of the role of Christian Religion teachers as pillars in the development of national education in accordance with the ideals of the 2045 Golden Indonesia Vision and Mission. The practical implications of the findings of this study can assist in designing more inclusive and values-oriented education policies to achieve Indonesia's future vision.